2017
DOI: 10.1017/s0021859617000594
|View full text |Cite
|
Sign up to set email alerts
|

The use of earth observation methods for estimating regional crop evapotranspiration and yield for water footprint accounting

Abstract: Remote sensing can efficiently support the quantification of crop water requirements included in the goal of assessing water footprints, which is to analyse how human activities or specific products relate to issues of water scarcity and pollution and identify how activities and products can become more sustainable from a water perspective. Remote sensing techniques have become popular in estimating actual crop evapotranspiration and hence crop water requirements in recent decades due to the advantages they of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Tall, dense crops, like tobacco, can block the wind, which decreases evaporation speed; thereby, increasing heat stress. 9,68 Although most farmworker studies estimate environmental heat stress through regional weather station measurements, authors from 2 US studies have reported microclimate (the area immediately surrounding the worker) measurements experienced by the farmworker. Set in Florida 69 and in California, 70 the study participants were not working in tobacco fields at the time of data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Tall, dense crops, like tobacco, can block the wind, which decreases evaporation speed; thereby, increasing heat stress. 9,68 Although most farmworker studies estimate environmental heat stress through regional weather station measurements, authors from 2 US studies have reported microclimate (the area immediately surrounding the worker) measurements experienced by the farmworker. Set in Florida 69 and in California, 70 the study participants were not working in tobacco fields at the time of data collection.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of estimating evapotranspiration (ET) is confirmed by many studies, such as [22][23][24][25][26][27] because its monitoring allows for implementing irrigation reducing water waste, optimizing the yield and preventing the risks of droughts. In response to these observational requirements, ESA, NASA and CNES/ISRO [28][29][30] plan the development of missions that can estimate the Land Surface Temperature (LST) at high spatial resolution and at high temporal frequency, through which it is possible to indirectly estimate the ET [28].…”
Section: Introductionmentioning
confidence: 99%